Circularly Polarized Low-Profile Antenna for Radiating Parallel to Ground Plane for RFID Reader Applications - Kittima Lertsakwimarn; Chuwong Phongcharoenpanich; Takeshi Fukusako (International Journal of Antennas and Propagation)
This paper presents a low-profile printed antenna with double U-shaped arms radiating circular polarization for the UHF RFID readers. The proposed antenna consists of double U-shaped strip structures and a capacitive feeding line to generate circular polarization. A part of the U-shaped arms is bent by 90° to direct the main beam parallel to the ground plane. From the results, -10 dB |S11| and 3 dB axial ratio of the antenna cover a typical UHF RFID band from 920 MHz to 925 MHz. The bidirectional beam is obtained with the maximum gain of 1.8 dBic in the parallel direction to the ground plane at the 925 MHz. The overall size of the proposed antenna including ground plane is 107 mm × 57 mm × 12.8 mm (0.33λ0 × 0.17λ0 × 0.04λ0).